Very preterm brain at rest: longitudinal social–cognitive network connectivity during childhood. Issue 4 (16th October 2021) - Mossad, Sarah I; Young, Julia M; Wong, Simeon M; Dunkley, Benjamin T; Hunt, Benjamin A E; Pang, Elizabeth W; Taylor, Margot J
Abstract: Very preterm (VPT: ≤32 weeks of gestational age) birth poses an increased risk for social and cognitive morbidities that persist throughout life. Resting-state functional network connectivity studies provide information about the intrinsic capacity for cognitive processing. We studied the following four social–cognitive resting-state networks: the default mode, salience, frontal-parietal and language networks. We examined functional connectivity using magnetoencephalography with individual head localization using each participant's MRI at 6 ( n  = 40) and 8 ( n  = 40) years of age compared to age- and sex-matched full-term (FT) born children ( n  = 38 at 6 years and n  = 43 at 8 years). VPT children showed increased connectivity compared to FT children in the gamma band (30–80 Hz) at 6 years within the default mode network (DMN), and between the DMN and the salience, frontal-parietal and language networks, pointing to more diffuse, less segregated processing across networks at this age. At 8 years, VPT children had more social and academic difficulties. Increased DMN connectivity at 6 years was associated with social and working memory difficulties at 8 years. Therefore, we suggest that increased DMN connectivity contributes to the observed emerging social and cognitive morbidities in school age.